2020
DOI: 10.1097/eja.0000000000001096
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic shutdown diagnosed with rotational thromboelastometry represents a moderate form of coagulopathy associated with transfusion requirement and mortality

Abstract: BACKGROUND Viscoelastic techniques have made it possible to describe specific fibrinolytic phenotypes (physiological, hyperfibrinolysis and shutdown) and to establish a relationship of these phenotypes with outcome. However, there remains a debate as to whether shutdown is a state of hypercoagulability or rather a coagulopathy with moderate fibrinolysis and fibrinogen consumption. OBJECTIVES Our objectives were to describe the relationship between fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…A majority of patients were male (335/420, 79.8%), of white race (227/420, 54.0%), and sustained blunt trauma (300/ 420, 71.5%). The median age was 37 (IQR: 26-55) years and the median ISS was 26 (IQR: [21][22][23][24][25][26][27][28][29][30][31][32][33]. Median time to TEG was 10.8 (IQR: 7.8-15.0) min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority of patients were male (335/420, 79.8%), of white race (227/420, 54.0%), and sustained blunt trauma (300/ 420, 71.5%). The median age was 37 (IQR: 26-55) years and the median ISS was 26 (IQR: [21][22][23][24][25][26][27][28][29][30][31][32][33]. Median time to TEG was 10.8 (IQR: 7.8-15.0) min.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations report different rates of admission coagulopathy, as measured by INR, in patients with hyperfibrinolysis who received TXA (18,19). Even among the fibrinolysis phenotypes there are likely intrinsic differences in underlying post-traumatic coagulation (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early low-maximum lysis is a poor determinant for the use of tranexamic acid since a significant proportion of patients will require a massive transfusion and die early; conversely, many other patients with low-maximum lysis on admission will require few blood products and revert to normal-maximum lysis at 24 h with low mortality. As described previously, early low-maximum lysis may signify an occult form of hyperfibrinolysis 9 or a moderate form of fibrinolysis and coagulopathy, 13,14 while a late low-maximum lysis state, associated with poor outcomes, may represent a true shutdown of the fibrinolytic system in response to a hypocoagulable state during bleeding. The underlying process of ROTEM hypofibrinolysis or the factors leading to it, rather than tranexamic acid per se, appears to determine the actual risk of developing multiorgan dysfunction syndrome.…”
Section: Critical Care Medicinementioning
confidence: 91%
“…Further biomarkers analyses and comparison with ROTEM patterns over time are required to elucidate the mechanisms underlying the fibrinolytic patterns, what ROTEM hypofibrinolysis represents in vivo, and whether each of the transition patterns described represent the same changes in the regulators of fibrinolysis. 13,14 Antifibrinolytics have been postulated to switch off normal levels of fibrinolysis, create a persistent fibrinolytic shutdown, and increase mortality and the incidence of multiorgan dysfunction syndrome and VTE, leading some institutions to limit tranexamic acid use to only those patients with ROTEM-diagnosed hyperfibrinolysis. 45,46 We have confirmed that prompt empiric administration of tranexamic acid is associated with reduced ROTEM hyperfibrinolysis and early deaths but importantly did not observe any increase in late mortality in patients who received tranexamic acid.…”
Section: Critical Care Medicinementioning
confidence: 99%